Geology, Rock Geochemistry and Ore Fluid Characteristics of the Brambang Copper-Gold Porphyry Prospect, Lombok Island, Indonesia. - Arifudin Idrus; Aji Syailendra Ubaidillah; I Wayan Warmada; Syafruddin Maula (UIR PRESS, 2021)
Brambang is one of the porphyry copper-gold prospects/deposits situated along eastern Sunda arc. This study is aimed to understand geological framework, alteration geochemistry and ore fluid characteristics of the prospect. Fieldworks and various laboratory analyses were performed including petrography, ore microscopy, rock geochemistry, chlorite chemistry and fluid inclusion microthermometry. The prospect is composed of andesitic tuff and diorite which are intruded by tonalite porphyries. Tonalite porphyries are interpreted as ore mineralisation-bearing intrusion. Various hydrothermal alterations are identified including potassic, phyllic, propylitic, advanced argillic and argillic types. Ore mineralisation is characterized by magnetite and copper sulfides such as bornite and chalcopyrite. Potassic alteration is typified by secondary biotite, and associated with ore mineralisation. Mass balance calculation indicates SiO2, Fe2O3, K2O, Cu and Au are added during potassic alteration process. Ore forming fluid is dominated by magmatic fluid at high temperature (450-600ºC) and high salinity (60-70 wt. % NaCl eq.). Hydrothermal fluid was diluted by meteoric water incursion at low-moderate temperature of 150-400ºC and salinity of 0.5-7 wt. % NaCl eq.